Merging repatronage behavior model (RBM) towards hypermarkets in Malaysia - Nezakati, Hossein; Ang, Siew Hui; Jofreh, Manoochehr (Asian Network for Scientific Information, 2014)
This study aimed to extend the existing research on repatronage behavior of customers in retailing industry. Retailing industry has become one of the sectors contributing a lot to gross domestic products of Malaysia in recent years. This study tries to investigate the relationship between service quality and customer satisfaction and identify factors influencing the repatronage behavior of customer. Using Descriptive Analysis, Pearson Correlation, Multiple Regression Analysis, F-test and Reliability Analysis, Statistical Processing SPSS Version 18.0 was applied to analyze the data. Results of the analysis showed that customer satisfaction, perceived value for money and store image are positively and significantly related to repatronage behavior of customers in hypermarket context. Overall, customer satisfaction played a much more significant role in affecting the repatronage intention of the customers. Similarly, service quality was shown as a predictor of customer satisfaction.